2009
DOI: 10.2319/013008-52.1
|View full text |Cite
|
Sign up to set email alerts
|

Dentoskeletal and Soft Tissue Effects of Mini-Implants in Class II division 1 Patients

Abstract: Mini-implants provided absolute anchorage to bring about significant dental and soft tissue changes in moderate to severe Class II division 1 patients and can be considered as possible alternatives to orthognathic surgery in select cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 16 publications
6
40
0
13
Order By: Relevance
“…18 When using a mini-implant or mini-plate to enhance anchorage, it has been reported that in a full fixed appliance, the anterior teeth retract but the posterior teeth show unwanted distal movement due to friction in the archwire/bracket interface. [19][20][21] Biocreative therapy was developed to enable retraction without involving the posterior segments and thus avoid such side effects. [6][7][8][9][10][11][12][13][14] The C-implant supports some osseointegration and accomplishes controlled anterior retraction with a ,1 mm change in the posterior unbracketed segments.…”
Section: Introductionmentioning
confidence: 99%
“…18 When using a mini-implant or mini-plate to enhance anchorage, it has been reported that in a full fixed appliance, the anterior teeth retract but the posterior teeth show unwanted distal movement due to friction in the archwire/bracket interface. [19][20][21] Biocreative therapy was developed to enable retraction without involving the posterior segments and thus avoid such side effects. [6][7][8][9][10][11][12][13][14] The C-implant supports some osseointegration and accomplishes controlled anterior retraction with a ,1 mm change in the posterior unbracketed segments.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, class II dental camouflage can be treated by extracting two premolars from the upper jaw and two from the lower jaw, and it can also be performed by extracting only the upper two premolar when there is no crowding on the lower dental arch (9,10). Anterior retraction can be done in two ways: "progressive retraction" in which canine and incisors are retracted in two stages or "en masse retraction" in which the anterior 6 teeth are retracted in one stage.…”
Section: Discussionmentioning
confidence: 99%
“…: Vous avez consacré de nombreuses publications [12,22,32,55,68,[70][71][72][73]87] et un ouvrage [50] aux ancrages orthodontiques temporaires. Comme pour tout dispositif mécanique, leur utilisation peut s'accompagner d'effets indésirables.…”
Section: Prise En Charge Des Hyperdivergencesunclassified